Uso da terapia anti-retroviral entre pacientes atendidos em dois serviços públicos de referência para o HIV/aids: impacto na qualidade de vida e ocorrência de sintomas de ansiedade e depressão - Lorenza Nogueira Campos (2008)
Introduction: The development of combination antiretroviral therapy (ART) has shifted the perception of HIV/AIDS from a fatal to a chronic and potentially manageable disease. ART is capable of improving survival, reducing morbidity and mortality, and improving quality of life (QL) of people living with HIV/AIDS. Symptoms of anxiety and depression are common among people with chronic diseases, including HIV infection. Those symptoms rank among the strongest predictors of non-adherence to antiretroviral therapy (ART), and can contribute to a worse immune and virologic response, faster progression to AIDS and a poor quality oflife. Moreover, considering that more efficacious treatments have been proposed not only to save lives but also to make them better, the impact of ART on the overall QL has become a major concern to the scientific community. Objectives: 1) To evaluate the effect of symptoms of anxiety and depression on the adherence to ART, and 2) to assess the impact of ART on the quality of life of HIV-infected patients in two public referral centers for AIDS, in Belo Horizonte, Infectious and Parasitic Diseases Training and Reference Center, from the City Health Department and Federal University of Minas Gerais, and Eduardo de Menezes Hospital, from the State Health Department, from 2001 to 2003. Methods: We conducted two main data analysis to answer both objectives. The ATAR Project, which main objective was to determine the incidence and associated factors to non-adherence to ART, included a baseline interview at the same day patients received their first antiretroviral prescription, i.e. before initiating ART, and three follow-up visits thereafter, at one, four and seven months later (first, second and third follow-up visits). In addition, quality of life and the occurrence of symptoms of anxiety and depression were assessed at the baseline interview and at the second follow-up visit, i.e. four months after initiating ART. In order to evaluate the occurrence of severe symptoms of anxiety and depression as risk factors for non-adherence to ART, we conducted a prospective concurrent analysis, using the Coxs proportional hazard model(objective 1). On the other hand, for the purpose of assessing the associated factors with better quality of life at month four of treatment, we carried on a cross-sectional analysis at the second follow-up visit, using the logistic regression model (objective 2). The level of significance considered was 0.05. Results: Prevalence of severe anxiety and depression symptoms before starting ART was 12.6% and 5.8%, respectively. Severe anxiety was a predictor of non-adherence to ART during follow-up period (RH=1.87; 95% CI=1.14-3.06), adjusted for low education, unemployment, alcohol use in the last month and symptoms of AIDS; while a history of injection drug use had borderline statistical significance with nonadherence. Moreover, overall QL was classified as very good and good by 16.4% and 50.0 of the participants, respectively, four months after initiating ART; while 24.4% classified their QL as neither poor nor good, 5.3% as poor and 3.8% as very poor. We observed a statistically significant improvement of overall QL comparing assessments at baseline and second visit. Logistic regression indicated that >8 years of education, none or mild symptoms of anxiety and depression, no ART switch, lower number of adverse reactions and better QL at baseline were independently associated with good/very good QL over four months of treatment. Conclusions: These findings suggest that using a brief screening procedure to assess anxiety and depression symptoms before initiating ART help identify individuals for interventions to improve adherence and quality of life. Additionally, our results highlight the importance of modifiable factors such as psychiatric symptoms and treatment-related variables that may contribute to a better QL among patients initiating treatment. Considering that a poor QL is related to non-adherence to ART, a careful clinical monitoring of those factors may contribute to guarantee the long-term effectiveness of antiretroviral regimens.